Scenario of research and intellectual production in the area of didactics in the southern of Brazil - Orlando Fernández Aquino; Vânia Maria de Oliveira Vieira; Marilene Ribeiro Resende; Maria Célia Borges (Universidade Estadual de Maringá, 2016)
The text was drawn from results of research carried out between 2010 and 2012. The objective was to understand the state of research and intellectual production in the area of Didactic in Southern Brazil. The documentary analysis methodology, working with documents available online was applied. The research was carried out with 9 Postgraduate Program in Education, 12 research lines, 115 professors, 244 research projects and 1730 publications. It was concluded that there is a great number of research and publication on the investigative field of Didactics and on the dimension of its foundation, but very little on the disciplinary and professional fields and on the conditions and ways of teaching. It is noteworthy that only a transformative practice can help change the reality of the school, the quality of teacher formation, of learning and mental development of the students.